Pemberian Pupuk Kompos dan Umur Pemotongan Titik Tumbuh Pada Pertumbuhan dan Hasil Tanaman Krisan (Chrysanthemum) - Delvianus Bili; I Gusti Made Arjana; Luh Kartini (Fakultas Pertanian, Universitas Warmadewa, 2019)
This study aims to obtain doses of compost fertilizer and age of cutting point growing on the growth and yield of chrysanthemum plants. The experimental design used was a randomized block design with a factorial pattern consisting of 2 factors. The first factor is the dosage of compost fertilizer with 4 levels ie 0 ton ha-1, 5 ton ha-1, 10 ton ha-1, 15 ton ha-1. The second factor is the age of cutting point of growth with 3 levels ie 1 week after planting, 2 weeks after planting, 3 weeks after planting. This experiment was conducted in Pancasari Village Sukasada District Buleleng Regency with altitude of 1,247 m above sea level, this research took place from May 9 until August 10, 2017. The highest weight of secondary branching stalk, obtained at interaction dose of 15 tons ha-1 compost with age cutting growth point 1 week after planting that is 98,27 gram increase equal to 55,65% compared dose of compost 0 ton ha-1 with age cutting point growing 1 week after planting that is 43,58 g.